Analysis of Service Officers Discover Program Yogyakarta International Airport (YIA) - Ismail; Amelia Puspa Tamara (Formosa Journal of Sustainable Research, 2023)
The purpose of this study is to find out what the YIA Discover Program is, to find out the services of officers in handling the Yogyakarta International Airport Discover program and to find out the constraints of officers in handling the Yogyakarta International Airport Discover program. The method in this study used qualitative analysis by taking samples using interview techniques, observation data and documentation. The results of this study are that as tour guide officers at Discover YIA so far they have not experienced too serious problems, maybe only minor obstacles, as one example is when officers handle quite a lot of participants (> 150 participants), but of course we also have a solution for this problem. As well as another obstacle when the participants we brought were children (under 5 years old) we were a little overwhelmed because there was also a lack of supervision